If
3 s i n 2 ( x ) + 7 c o s 2 ( x ) = 1 0 − s i n ( 2 x ) + 1
find tan(x), if tan(x) = − b a , find a+b
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rearranging the two sides of the equation, noting that sin 2 x = 2 sin x cos x
3 0 7 sin 2 x + 5 sin x cos x + 7 0 3 cos 2 x = 0
⇔ 3 0 7 sin 2 x + 5 sin x cos x + 7 cos 2 x − 1 0 1 = 0
As cos x = 0 doesn't satisfy the equation, divide both sides by 2 1 0 cos 2 x gives us:
4 9 tan 2 x + 4 2 tan x + 9 = 0 , or: ( 7 tan x ) 2 + 2 × 3 × 7 tan x + 3 2 = 0
⇔ ( 7 tan x + 3 ) 2 = 0
⇔ tan x = 7 3
So, a + b = 3 + 7 = 1 0
Problem Loading...
Note Loading...
Set Loading...
3 t a n 2 x + 7 1 = 1 0 − 2 t a n x + 1 + t a n 2 x
= 4 9 t a n 2 x + 4 2 t a n x + 9 = 0
( 7 t a n x + 3 ) 2 = 0
t a n x = − 7 3